L’analyse De Préposition dans Youyou et Vive Le Cirque D’album Par Pierre Lozère - Kenwangi, Kezia; Endang Ikhtiarti; Indah Nevira Trisna (Franconesia, 2024)
This research aims to analyze the types of prepositions and the meaning functions of prepositions in French children's songs from YouYou’s album which consists of 7 songs and Vive Le Cirque which consists of 6 songs. The method used is descriptive qualitative method. The data collection step is that the researcher divides the elements by sentence with the BUL method (Bagi Unsur Langsung). Then analyze based on the types of prepositions. The next step to find out the function of prepositions is to translate the array to be categorized according to its function. The final step is to enter the data obtained into the data classification table. The data analysis method in this research is after classifying the elements included in the preposition after collecting the data. Researchers sort out which elements are included in the preposition using the basic technique of PUP (Pilah Elemen Penentu). The next step is to reread the song array with the advanced technique of bookmark reading technique. Understanding each array that has been translated previously with the contextual translation technique which translates based on the context per array, the next step, after obtaining the meaning of each array, the next step classifies the meaning according to the function of preposition meaning, and continued with the HBS technique.